The Use of Kahoot in Writing Skills in Junior High School: Penggunaan Kahoot dalam Keterampilan Menulis di Sekolah Menengah Pertama - Romatullah, Sitti; Santoso, Dian Rahma (Universitas Muhammadiyah Sidoarjo, 2023)
Writing skill is a way to express and build the ideas into written form. In 4.0 era, which technology is to support the education, one of which is by using Kahoot in learning process. The methodology used in this research was the experimental quantitative research with the paired sample t-test. The research population was 319 eigh grade students. Then, the research sample was 8E consisting of 36 students at SMPN 3 Sidoarjo in the academic year of 2021/2022. The result of the data presented that, there was significant different score between pre-test and post-tes. The mean pre-test was 54.25 and the the mean of post-test was 68.78. The significant value of the research was 0.000 < significant level 0.05. therefore, it showed there is an effect of Kahoot for learning writing skill recount text of the eight grade students at SMPN 3 Sidoarjo